The Test of Grinder Spacing on the Quality Gnetum of Gnemon chips On the Grain Chips Forming Tool - Rio Baruna Sirait; Ainun Rohanah; Saipul Bahri Daulay (Universitas Sumatera Utara, 2016)
This study was aimed to test the effect of spacing on grinder cylinder to the quality of the chips on grain chips .The results showed that the resulting Gnetum gnemon chips categorized on the test grinder quality of 2 , the shape is not uniform, white browny , thickness uniform , and can be fried immediately after they are printed . Highest yield was produced in spacing of cylinder grinder of 3 mm that is equal to 83 % and the lowest in spacing of cylinder grinder 1 mm that is equal to 78.2 %. The highest processing capacity was found in the spacing of cylinder grinder of 3 mm that is equal to 3.01 kg / hour and the lowest was found in the spacing of cylinder grinder 1 mm that is equal to 2.61 kg / h . The best organoloptic value was found in the spacing of cylinder grinder 1 mm. Keywords : Distance cylinder, Quality Chips